2022
DOI: 10.1038/s41419-022-04531-3
|View full text |Cite
|
Sign up to set email alerts
|

HucMSC exosomes promoted imatinib-induced apoptosis in K562-R cells via a miR-145a-5p/USP6/GLS1 axis

Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm with increasing incidence worldwide. Growing evidence suggests that ubiquitin-specific proteases (USPs) play a role in cancer treatment. Dysregulation of miR-146a has been found in both adult and pediatric patients with acute leukemia. Knockdown of glutaminase-1 (GLS1) resulted in inhibition of tumor growth. However, the role of miR-146a-5p/USP6/GLS1 in leukemia and chemoresistance of leukemia cells remains to be elucidated. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…MiRNAs have been recognized as key regulators of cancer chemoresistance. Previous studies have reported that hsa-miR-145-5p and hsa-miR-203a-5p hold the ability to overcome IM resistance in CML cells. Likewise, the efficacy of these two miRNA mimics in overcoming IM resistance has been verified in our previously published study . The study utilized the MTT assay to assess the effects of hsa-miR-145-5p and hsa-miR-203a-5p, both individually and in combination with IM (IM + hsa-miR-145-5p and IM + hsa-miR-203a-5p).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…MiRNAs have been recognized as key regulators of cancer chemoresistance. Previous studies have reported that hsa-miR-145-5p and hsa-miR-203a-5p hold the ability to overcome IM resistance in CML cells. Likewise, the efficacy of these two miRNA mimics in overcoming IM resistance has been verified in our previously published study . The study utilized the MTT assay to assess the effects of hsa-miR-145-5p and hsa-miR-203a-5p, both individually and in combination with IM (IM + hsa-miR-145-5p and IM + hsa-miR-203a-5p).…”
Section: Resultsmentioning
confidence: 68%
“…So based on the last publication, our current objective is to investigate several other metabolic pathways in addition to the glutathione metabolism that may also contribute to the development of IM resistance. Moreover, we investigated whether the reversion of IM resistance following hsa-miR-145-5p or hsa-miR-203a-5p transfection might be linked to a reversal of the metabolic profile, referencing findings from various studies where the enforced expressions of these miRNAs resulted in the reversal of IM resistance in leukemic cells. …”
Section: Introductionmentioning
confidence: 99%
“…For example, microRNA-503-3p, microRNA-431-5p, and miR-145a-5p in exosomes of MSC can play a role in suppressing tumors. [25,41,42] However, whether circRNAs in exosomes also plays a role in anticancer activity is currently unclear. Next, we found that the expression of circ_0037104 was significantly reduced in CCA, which could significantly inhibit the occurrence and development of CCA.…”
Section: Discussionmentioning
confidence: 99%
“…IM serves an important role in CML treatment and IM resistance is also an obstacle to CML treatment. A previous study showed that ubiquitin-specific protease is significantly up-regulated in IM-resistant clinical samples; miR-146a-5p down-regulated the IM resistance of CML, human umbilical cord mesenchymal stem cell-derived exosomes can promote IM-induced apoptosis through miR-145a-5p/USP6,indicating the potential role of miR-146a-5p in leukaemia chemoresistance ( 94 ). A study has confirmed that miR-328 is significantly decreased in IM-resistant patients, where overexpression of miR-328 sensitizes drug-resistant tumour cells to IM.…”
Section: Exosomes and Drug Resistancementioning
confidence: 97%